Impact of the financial structure on bankruptcy risk in the economic enterprise: an empirical analysis study at Omar Ben Omar Mills from 2010 to 2020 - khalfallaoui, ikhlas; medjellekh, salim; bechichi, walid (Journal of Research in Finance and Accounting, 2022)
This study aims to describe, analyze, and measure the impact of the financial structure on on risk of bankruptcy at Omar Ben Omar Mills by applying the VAR model from the period (2010 to 2020). The financial structure was determined based on the debt ratio of total assets, the debt ratio of property rights, the ratio of long-term debt to total assets and the ratio of short-term debt to total assets . Also, the risk of bankruptcy was measured by using the Probit method The study concluded that there are significant relationships with different statistical significance, positive and negative, between the variables of the financial structure and the risks of bankruptcy for the three delays. The analysis also showed the severity of the relationship between dependent variables and independent variables throughout the study period. The study also revealed that Granger causation does not work in either direction between the financial structure and the risk of bankruptcy.